2011
DOI: 10.1016/j.ajpath.2010.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells Contribute to the Vascularization of Endometriotic Lesions

Abstract: Endometriosis is a frequent gynecological disease that is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 31 publications
(29 reference statements)
4
45
0
2
Order By: Relevance
“…Besides angiogenesis, vascularization of endometriotic lesions also involves vasculogenesis, which is defined as de novo formation of microvessels from circulating endothelial progenitor cells [41][42][43]. Although not further analyzed in the present study, the suppression of this process may have been an additional mechanism contributing to the reduced functional capillary density of endometriotic lesions in quinalizarin-treated animals.…”
Section: Discussionmentioning
confidence: 64%
“…Besides angiogenesis, vascularization of endometriotic lesions also involves vasculogenesis, which is defined as de novo formation of microvessels from circulating endothelial progenitor cells [41][42][43]. Although not further analyzed in the present study, the suppression of this process may have been an additional mechanism contributing to the reduced functional capillary density of endometriotic lesions in quinalizarin-treated animals.…”
Section: Discussionmentioning
confidence: 64%
“…15 In this model, the bone marrow of FVB/N wild-type mice is replaced by bone marrow from FVB/N-TgN (Tie2/GFP) 287 Sato mice. For this purpose, the mice are lethally irradiated, which affects the physiological function of the ovary.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,28 Recent reports provide evidence that the vascularization of endometriotic lesions is not only driven by angiogenesis but also involves vasculogenesis. 14,15 The latter mechanism of blood vessel development is characterized by homing of circulating EPCs to the lesions, where they are incorporated into the Detailed information about the individual genes is provided in GenBank (http://www.ncbi.nlm.nih.gov/genbank) using the provided accession numbers. RT-qPCR, quantitative RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When TEMs are specifically depleted, endothelial cells fail to organize effectively in neovessels and undergo programmed cell death, leading to disruption of the lesions. The preferential localization of TEM in perivascular areas 16 and their relative proximity to endothelial cells may provide survival and growth signals to endothelial cells, and possibly also to endothelial progenitor cells 55 Indeed, recent gene profiling studies of tumor-derived TEMs and other TAM subsets showed that TEMs express several proangiogenic and survival factors, including insulin-like growth factor 1. 20 Previous studies have indicated that macrophage alternative activation is critical for endometriosis.…”
Section: Discussionmentioning
confidence: 99%